TRANSFORMATION INTO THE â€œGODâ€: STUDY OF CRITICâ€“ELABORATIVE AXIOLOGY OF ISLAMIC EDUCATION WITH PHILOSOPHICAL SUFISM - Umiarso, Umiarso (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2019)
AbstractEmbody an al-insan al-kamil is the ultimate aim of Islamic Education and philosophical Sufism. This human construction can be emerged through education that internalizes divine natures in the subject of education. Therefore, between Islamic educational philosophic has dialectical relation to embody human into â€œGodâ€. Therefore, this article focused on the construction of Islamic education in realizing al-insan al-kamil (a complete man) which has similarities with the goals of philosophical Sufism. The aim is to analyze and understand the construction of human transformation efforts into "God" as the axiological orientation of Islamic education and philosophical Sufism. Hence, the current article used a qualitative approach with a literature review of research type to elaborate the focus. Meanwhile, the data analysis used was content analysis and interpretation methods. Islam that integrated to the aim of philosophical Sufism may encourage the born of ideal human beings (al-insan al-kamil). A human that has completeness in the aspects of intellectuality, emotional, and spirituality as the figure of caliph (khalifah) or Abdullah. This human model in the formulation of philosophical Sufism was a human who has â€œmergedâ€ with God; or human who transforms themselves into â€œGodâ€. The practical implications of this research, Islamic education on the theological-philosophical dimensions must continue to unite axiological orientation (Islamic education and philosophical Sufism) to be applied in the process of Islamic religious learning.Abstrak Melahirkan al-insan al-kamil merupakan tujuan tertinggi (ultimate aim) dari pendidikan Islam dan tasawuf falsafi. Konstruksi manusia ini bisa dimunculkan melalui pendidikan yang menginternalisasikan sifat-sifat ketuhanan dalam diri subjek pendidikan. Karenanya, antara filsafat pendidikan Islam dengan tasawuf falsafi memiliki relasi dialektis untuk mewujudkan manusia menjadi â€œTuhanâ€. Oleh sebab itu, artikel ini fokus pada konstruksi tujuan pendidikan Islam dalam mewujudkan al-insan al-kamil yang memiliki kesamaan dengan tujuan tasawuf falsafi. Tujuannya, untuk menganalisis dan memahami konstruksi upaya transformasi manusia menjadi â€œTuhanâ€ sebagai orientasi aksiologis pendidikan Islam dan tasawuf falsafi. Karenanya, artikel ini menggunakan pendekatan kualitatif dengan jenis penelitian kepustakaan untuk mengurai fokus dan tujuan riset tersebut. Sedangkan analisa data digunakan metode content analysis dan interpretasi. Artikel ini menyimpulkan bahwa proses mewujudkan tujuan pendidikan Islam yang diintegrasikan dengan tujuan tasawuf falsafi mampu mendorong lahirnya manusia ideal (al-insan al-kamil). Manusia yang memiliki kesempurnaan pada aspek intelektualitas, emosional, dan spiritualitas sebagai sosok khalifah maupun abdullah. Manusia model ini di dalam formulasi tasawuf falsafi merupakan manusia yang telah â€œmenyatuâ€ dengan Tuhan; atau manusia yang mentransformasi diri menjadi â€œTuhanâ€. Implikasi praktis riset ini, pendidikan Islam pada dimensi teologis-filosofis harus terus menyatukan orientasi aksiologis (pendidikan Islam dan tasawuf falsafi) untuk diaplikasikan dalam proses pembelajaran pendidikan agama Islam.